Macroprudential Regulation of Credit Booms and Busts : The Case of Croatia - Kraft, Evan; Galac, Tomislav (2012)
Croatia employed macroprudential measures to manage credit growth and capital inflows during the boom years of the 2000s, including reserve requirements on loan growth, a marginal reserve requirement on increases in foreign liabilities, foreign exchange liquidity minima, and elevated capital adequacy ratios. Although quantitative analysis is complicated by substantial overlaps among measures, the econometric results in this paper suggest that the measures were most effective in requiring banks to hold high liquidity and capital buffers, and less effective in slowing credit growth and capital inflows. Larger buffers seem to have helped Croatian banks weather the financial crisis, making the adjustments to capital and liquidity during the crisis smaller.